THE IMPACT OF THE CHANGEOVER TO THE EURO FOR EASTERN EUROPEAN COMPANIES - NICOLAE MARINESCU (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2018)
The introduction of the euro as a single currency in Eastern European countries, the new member states of the European Union, has sparked, and still sparks, a great deal of debate concerning the effects that arise from this changeover. Although macroeconomic effects of switching to the euro have been analyzed extensively, microeconomic effects have received far less attention. This paper tries to bring a contribution in this field and fill the existing gap in the literature. It investigates the impact of the introduction of the euro on Eastern European companies. Based on a thorough desktop research, the aim of the paper is twofold. Firstly, it shows the estimated effects companies will experience when their respective country will make the changeover to the euro. Secondly, it analyzes the measures these companies will have to take so as to ensure an efficient transition to the euro, by trying to reap the benefits and mitigate hardships linked to this move. The results of the analysis consist in a kit of operational measures, valuable to owners and managers of Eastern European companies who want to prepare properly for the changeover to the euro.